Effect of Strength Enhancement of Soil Treated with Environment-Friendly Calcium Carbonate Powder. (4th February 2014) - Park, Kyungho; Jun, Sangju; Kim, Daehyeon
Abstract : This study aims to investigate the effects of the strength improvement of soft ground (sand) by producing calcium carbonate powder through microbial reactions. To analyze the cementation effect of calcium carbonate produced through microbial reaction for different weight ratios, four different types of specimens (untreated, calcium carbonate, cement, and calcium carbonate + cement) with different weight ratios (2%, 4%, 6%, and 8%) were produced and cured for a period of 3 days, 7 days, 14 days, 21 days, and 28 days to test them. The uniaxial compression strength of specimens was measured, and the components in the specimen depending on the curing period were analyzed by means of XRD analysis. The result revealed that higher weight ratios and longer curing period contributed to increased strength of calcium carbonate, cement, and calcium carbonate + cement specimens. The calcium carbonate and the calcium carbonate + cement specimens in the same condition showed the tendency of decreased strength approximately 3 times and two times in comparison with the 8% cement specimens cured for 28 days, but the tendency of increased strength was approximately 4 times and 6 times in comparison with the untreated specimen.